(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2024)
The paper examined the Impact of Information and Communication Technology on Primary School Administration in Northern Part of Kaduna State Nigeria. The research question are inline with Research objective and Research hypothesis, the study is descriptive in nature. The research is limited to the primary schools located at the Northern Part of Kaduna State Nigeria. The population of the study is one thousand one hundred and twenty-six (1126) while the sample size is two hundred and thirty-four (234), the instruments used was questionnaire for data collection. A total number of two hundred and thirty-four was distributed to the respondent (School support officers and the head-teachers) The data was analyzed and interpreted with the use of t-test statistical tool, hypothesis testing is at p>0.05 level of significant, where any t- calculated value below 0.05 is rejected. The results of the study reveals that there is no significant difference on the opinions of head teachers and School Supports officers on the Impact of ICT on Primary School Administration in Northern Part of Kaduna State. In conclusion the study shows that the use of ICT in the Administration of Primary Schools has great impact as it is highly vital so as to have effective and efficient service delivery in the to meet up with the new world. It was recommended that school administrators should develop the way on how to provide knowledge and skills of ICT in management of Primary Schools and it has been suggested that the government should ensure that they provide computers in the schools and also to engage the teachers and the support system officers to go for inservice training and workshop from time to time, so as to enhance ICT knowledge